Mysid (Malacostraca: Mysida) Diversity of Türkiye - BAKIR, KEREM; ÖZBEK, MURAT; TOPKARA, ESAT TARIK (Mediterranean Marine Science, 2025)
Mysid crustaceans are key components of aquatic ecosystems, yet their diversity is still not well documented in many regions. This study presents an updated and comprehensive list of Mysida species recorded in Türkiye, raising the total to 37 species and one subspecies. The list includes four species reported for the first time in the country (Heteromysis microps, Heteromysis norvegica, Hemimysis lamornae, and Pyroleptomysis cf. peresi) and excludes Mysis relicta, which was previously misidentified. To support accurate species recognition, a detailed species identification key combining classical descriptions with recent taxonomic references has been developed. Ecological differences among mysid species shape their distribution patterns: some are widespread, while others are rare and restricted to specific regions such as the Gulf of İzmir and the Sea of Marmara. The scarcity of records in certain areas likely reflects limited targeted research. Genera like Diamysis, Heteromysis, and Leptomysis remain understudied because of their subtle morphological features, underscoring the need for focused biodiversity surveys and genetic analyses to uncover potentially overlooked species in Türkiye. Overall, this study enhances current knowledge of Türkiye’s mysid fauna, provides a foundation for future taxonomic and ecological research, and contributes to the broader documentation of national biodiversity.